2019
DOI: 10.3389/fcimb.2019.00346
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Gut Microbiota and Metabolites Signature in Patients With Irritable Bowel Syndrome

Abstract: Background and Aims: Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder. However, the underlying mechanism of IBS is not fully understood. The aim of this study was to investigate potential mechanism and novel biomarkers of IBS through evaluation of the metabolomic and microbiologic profile.Methods: Fecal samples were collected from 15 irritable bowel syndrome patients and 15 healthy controls. By using gas chromatography coupled to time-of-flight mass spectrometry (GC-TOFMS) and 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 49 publications
5
48
0
Order By: Relevance
“…From the perspective of bacterial taxonomic alterations, most high-throughput data showed a decreased abundance of phyla Firmicutes and increased Bacteroidetes in IBS microbes in agreement with our results [21,24]. Vast studies demonstrated that Bifidobacterium and Lactobacillus were less abundant in IBS-D, whereas Clostridium, Escherichia coli and Enterobacter were often increased [19,20,[24][25][26]. Faecalibacterium (or F. prausnitzii) abundance in IBS increased in some studies [27], but constant or decreased in others [24].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…From the perspective of bacterial taxonomic alterations, most high-throughput data showed a decreased abundance of phyla Firmicutes and increased Bacteroidetes in IBS microbes in agreement with our results [21,24]. Vast studies demonstrated that Bifidobacterium and Lactobacillus were less abundant in IBS-D, whereas Clostridium, Escherichia coli and Enterobacter were often increased [19,20,[24][25][26]. Faecalibacterium (or F. prausnitzii) abundance in IBS increased in some studies [27], but constant or decreased in others [24].…”
Section: Discussionsupporting
confidence: 89%
“…Our current study compared the faecal microbiota from IBS-D and healthy groups. Simpson index demonstrated decreased faecal biodiversity, whereas Ace and Chao indices showed higher microbial richness in IBS-D group, supported by human and animal researches [17][18][19]. Analysis of similarity (ANOSIM), PCoA and hierarchical clustering analysis based on Bray-Curtis distance showed no significant difference of β-diversity between groups.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies have shown that patients with IBS‐D have comparatively higher levels of free serum tryptophan than those in HC . Phenylalanine was identified as a major fecal metabolite in IBS, and phenylalanine metabolism was the most relevant pathway influenced by IBS . Phenylalanine is liphophilic and aromatic amino acid which influence membrane diffusion and transportation .…”
Section: Discussionmentioning
confidence: 99%
“…Results showed IBS patients had a significantly differential metabolite profile as compared to healthy controls. Some clusters of fecal metabolites or microorganisms were significantly correlated with the severity of IBS symptoms, such as the frequency of abdominal pain/discomfort and the number of bowel movements [42]. Central nervous system signals are transmitted to the gut by neuroendocrine neurotransmitters (serotonin, corticotropin-releasing hormone, cholecystokinin, and somatostatin) which are produced in the gut by immune and enterochromaffin cells to alter microbiota behavior [43].…”
Section: Microbiota and The Gut-brain Axismentioning
confidence: 99%